Pengaruh Harga dan Kualitas Pelayanan Terhadap Minat Beli Konsumen pada Pakaian Distro di Bandar Lampung - Budiana, I Gede; Rahayu, Ni Putu Widhia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Business actors in the clothing distribution industry must pay attention to the needs, desires, and expectations of consumers in order to cultivate strong purchasing interest. Therefore, effective strategies are required to attract consumers' interest in purchasing clothing products at distros. This study aims to empirically examine the influence of price and service quality on the buying interest of consumers purchasing distro clothing in Bandar Lampung. A quantitative approach was employed, with the population consisting of clothing consumers in the city of Bandar Lampung. The accidental sampling technique was utilized to select samples, with 96 consumer respondents who purchased distro clothing in the city of Bandar Lampung. Data were collected through various methods, including literature review, documentation, observation, interviews, and questionnaires. Data analysis was conducted using multiple linear regression tests, correlation coefficient tests, t tests, F tests, and R² tests. The results showed that price and service quality significantly influence the buying interest of consumers at distro clothing stores in Bandar Lampung. Together, these variables also significantly influence consumers' buying interest. The simultaneous F test results indicated that price and service quality together significantly influence consumers' buying interest at distro clothing stores in Bandar Lampung, with price and service quality contributing 26.9% to consumers' buying interest at distro clothing stores in Bandar Lampung.